(untitled) (Revista Lusófona de Educação, 2026)
University institutions play a strategic role by including educational policies that promote social integration and student involvement in their management systems. This process aims to help them understand the reality in which they find themselves and develop the skills to anticipate, articulate and implement solutions that contribute to more sustainable societies and lower dropout rates. The aim of this study was to analyse the social integration and academic involvement of students in higher education in Portugal. The participants were 342 university students aged between 17 and 63, mostly women, attending the 2nd year of 1st cycle courses. The sample was taken in the 2023/2024 academic year. The Questionnaire on Social Integration in Higher Education (QISES) was applied, with 20 items, a likert scale and five factors. The results suggest that higher education institutions could adopt active educational policies that promote the social integration and well-being of students, with special attention to strengthening interpersonal relationships with colleagues, for a more adjusted social integration. It is suggested that educational policies that favour an inclusive academic environment and promote open communication between students and teachers should be valued as implications.